Inactivation of Spry2 accelerates AKT-driven hepatocarcinogenesis via activation of MAPK and PKM2 pathways - Wang, Chunmei (2012)
BACKGROUND & AIMS: Aberrant activation of the AKT oncogenic pathway and downregulation of the Sprouty 2 (Spry2) tumor suppressor gene are frequently observed molecular events in human hepatocarcinogenesis. The goal of the present study was to investigate the eventual biochemical and genetic crosstalk between activated AKT and inactivation of Spry2 during liver cancer development by using in vivo and in vitro approaches. METHODS: Activated AKT and/or Spry2Y55F, a dominant negative form of Spry2, were overexpressed in the mouse liver via hydrodynamic gene delivery. Histological and biochemical assays were applied to characterize the molecular features of AKT and AKT/Spry2Y55F liver tumors. The human HLE hepatocellular carcinoma (HCC) cell line, stably overexpressing AKT, was transfected with Spry2Y55F to study the molecular mechanisms underlying hepatocarcinogenesis driven by Spry2 loss. RESULTS: Spry2Y55F overexpression significantly accelerated AKT induced hepatocarcinogenesis in the mouse. AKT/Spry2Y55F liver lesions had increased proliferation and glycolysis and decreased lipogenesis when compared with AKT corresponding lesions. At the molecular level, AKT/Spry2Y55F HCCs exhibited a significantly stronger induction of activated mitogen-activated protein kinase (MAPK) and Pyruvate Kinase M2 (PKM2) pathways than in AKT corresponding lesions. This phenotype was reproduced in HLE cells overexpressing AKT following transfection with Spry2Y55F. Furthermore, we found that concomitant suppression of the MAPK cascade and PKM2 strongly inhibited the growth induced by Spry2Y55F in AKT-overexpressing cells. CONCLUSIONS: Inactivation of Spry2 accelerates AKT induced hepatocarcinogenesis via activation of MAPK and PKM2 pathways.